Case Report: A Novel Mutation Identified in CHST14 Gene in a Fetus With Structural Abnormalities - Zhou, Yuan-Yuan; Du, Yu-Fang; Lu, Qing; Zhai, Xiu-Zhang; Shi, Ming-Fang; Chen, Dan-Yun; Liu, Sun-Rong; Zhong, Ying (Frontiers in Genetics, 2022)
Background Musclecontractile Ehlers-Danlos syndrome (mcEDS) is a rare heritable connective tissue disease with various symptoms. The diagnosis of mcEDS is difficult because of the large overlap of clinical symptoms between different EDS subtypes. Methods We performed karyotype analysis, gene copy number variation detection, whole exome sequencing and Sanger sequencing to reveal the underlying genetic etiology of a fetus with structural abnormalities in feet and kidneys. Results A likely pathogenic mutation [NM_130468.3 c.958C>T (p.Arg320*)] and an uncertain significance mutation [NM_130468.3 c. 896A>G (p.Tyr299Cys)] were identified in the carbohydrate sulfotransferase14 (CHST14) gene by whole exome sequencing and validated by Sanger sequencing. Conclusion The two identified mutations appear highly likely to be the genetic causes of the fetal structural abnormalities.